Transcription dynamics of heat shock proteins in response to thermal acclimation in Ostrinia furnacalis - Quan, Yudong; Wang, Zhenying; Wei, Hongyi; He, Kanglai (Frontiers in Physiology, 2022)
Acclimation of abiotic stress plays a critical role in insect survival, adaption, and evolution, particularly in the increasingly frequent extreme climate events due to ongoing climate change. Heat shock proteins (HSPs) are evolutionarily conserved critical molecular chaperones that function to avert the misfolding and denaturation of proteins caused by abiotic and biotic stressors such as heat shock. Understanding the relation between thermal acclimation and expression of specific HSPs is essential to address the precise functions of HSPs families in adaptation. In this study efforts have been carried out to investigate this issue using Asian corn borer Ostrinia furnacalis, one of the most important corn pests in China, where is easy suffer the heat waves in summer. Larvae are induced HSPs at least more 33oC temperature. Later larvae are performed with a drastic thermal treatment (43 oC, 2 h) stress firstly, and recovered in the rearing environment (27 oC) for 0, 0.5, 1, 2, 4, 6, and 8 h. At the recovery time 0.5 - 4 h, the most population tolerates less around 1 - 3 h than without recovery (at 0 h) suffering the continuous heat stress (43 oC). There is no difference in the heat tolerance since recovery 6 h, which showed similar expression level of HSPs in control. However, a significantly thermal tolerance was observed over 8 h of the recovery time, and higher level of HSP70. In addition, dynamics of transcriptional expression of HSP60 and HSC70 (heat shock cognate protein 70) during the thermal tolerance didn’t show significant effect. HSP70 or HSP90 were significantly up-regulated within 1 - 2 h sustained heat stress (43 oC), but didn’t last the peak more than 4 h, would decline at 6 h. Our finding revealed an extreme thermal stress induced quick dynamics of HSP70 or HSP90 expression could be interpreted as an adaptation to the drastic and rapid temperature variation. The regulation of HSP70 and HSP90 would last 4 - 6 h. Meanwhile the thermal tolerance of lavae would be significantly enhanced after 6 h and more of recovery, and possibly regulated by HSP70.